Further Training for the unemployed : what can we learn about dropouts from administrative data? - Waller, Marie [Verfasser] (My University, 2008)
"One out of five participants of further training programs in Germany drops out of the program. Studies on the employment effects of these measures usually consider the start of a program as the treatment and do not deal with the question if the program has been completed. By contrast, this paper focuses on the distinction between dropping out and completing a program. It first discusses how to identify dropouts in the German Integrated Employment Biographies Sample, which is possible after having corrected measurement error in the registered end of participation. Second, the occurrence of dropouts is studied - how often and when do people drop out and what makes a dropout more likely. Third, the employment prospects of dropouts are analyzed descriptively." (author's abstract, IAB-Doku) ((en))
Keywords: G 1.2 Arbeitsmarkt; S 2.3.2 Programme in der Berufsbildung; L 6.2.3 Evaluation; Arbeitsmarktpolitik; Beschäftigungseffekte; Berufliche Weiterbildung; Ausbildungsabbruch; Prozessproduzierte Daten; Wirkungsforschung